Association of temperature management strategy with fever in critically ill children after out-of-hospital cardiac arrest - Kadden, Micah; Zhang, Anqing; Shoykhet, Michael (Frontiers in Pediatrics, 2024)
To determine whether ICU temperature management strategy is associated with fever in children with return of spontaneous circulation (ROSC) after out-of-hospital cardiac arrest (OHCA). We conducted a single-center retrospective cohort study at a quaternary Children's hospital between 1/1/2016-31/12/2020. Mechanically ventilated children (<18 y/o) admitted to Pediatric or Cardiac ICU (PICU/CICU) with ROSC after OHCA who survived at least 72 hours were included. Primary exposure was initial PICU/CICU temperature management strategy of: 1) passive management; or 2) warming with an air-warming blanket; or 3) targeted temperature management with a heating/cooling (homeothermic) blanket. Primary outcome was fever (>=38°C) within 72 hours of admission. Over the study period, 111 children with ROSC after OHCA were admitted to PICU/CICU, received mechanical ventilation and survived at least 72 hours. Median age was 31 (IQR 6 - 135) months, 64% (71/111) were male, and 49% (54/111) were previously healthy. Fever within 72 hours of admission occurred in 51% (57/111) of patients. The choice of initial temperature management strategy was associated with occurrence of fever (Chi squared 2 = 9.36, df = 2, p = 0.009). Fever occurred in 60% (43/72) of patients managed passively, 45% (13/29) of patients managed with the air-warming blanket and 10% (1/10) of patients managed with the homeothermic blanket. Compared to passive management, use of homeothermic, but not of air-warming, blanket reduced fever risk (homeothermic: Risk Ratio (RR) = 0.17, 95%CI 0.03 - 0.69; air-warming: RR = 0.75, 95%CI 0.46 - 1.12). To prevent fever in one child using a homeothermic blanket, number needed to treat (NNT) = 2.